Periodic boundary value problem for second order integro-ordinary differential equations with general kernel and Carathéodory nonlinearities - Juan J. Nieto (International Journal of Mathematics and Mathematical Sciences)
We study the existence of solutions for the periodic boundary value problem for some second order integro-differential equations with a general kernel. Also we develop the monotone method to approximate the extremal solutions of the problem.